PENERAPAN PERATURAN MENTERI HUKUM DAN HAM NO 32 TAHUN 2018 PADA UNIT PELAKSANA TEKNIS PEMASYARAKATAN - Danang Wisnu Santoso (Journal Publicuho, 2021)
The purpose of this paper is to examine the application of the regulation of the Minister of Law and Human Rights No. 32 of 2018 concerning the treatment of elderly prisoners and convicts, where the regulation can be used as a reference for the Correctional Technical Implementation Unit to carry out services for elderly inmates.The research method uses a qualitative descriptive approach. trying to explain by describing the conditions that exist in the Technical Implementing Unit in providing services to elderly prisoners and comparing it with PermenKUMHAM No. 32 of 2018. The results of the study explain that the implementation of PermenKumHAM No. 32 of 2018 in the Correctional Technical Implementation Unit has not been evenly implemented. , but that does not mean that it is not carried out at all in the technical implementing unit.